Children's Work in African Agriculture The Harmful and the Harmless - Sumberg, James; sabates-wheeler, rachel (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book examines children's involvement in African agricultural work. It argues that framing all children's engagement in economic activity as 'child labour', with all the associated negative connotations, is problematic. The conceptual and case-based chapters reframe the debate about children's work and harm in rural Africa with the aim of shifting research, public discourse and policy so that they better serve the interest of rural children and their families.